Instructional Supervision of Master Teachers: Its Critical Role in Advancing Teachers’ and Learners’ Performance (American Journal of Education and Technology, 2025)
This study examined the role of master teachers in improving the performance of proficient teachers and learners, focusing on instructional supervision across Key Result Areas (KRAs) during the school year 2024-2025. Utilizing a quantitative descriptive-correlational design, data were gathered from 95 master teachers and 75 school heads across public elementary schools in the second district of Surigao del Sur. The study also assessed elementary teachers’ Individual Performance Commitment and Review Form (IPCRF) ratings and learners’ academic performance through Mean Percentage Scores (MPS). Results indicated that instructional supervision was highly manifested across all KRAs, with an overall mean score of 4.449. The highest-rated domain was Professional Engagement, Personal Growth, and Professional Development (M=4.515), highlighting educators’ commitment to continuous learning. However, correlation analysis revealed no significant relationship (p>0.05) between teachers’ performance and learners’ academic performance. This finding suggests that while instructional supervision is well-practiced, it does not directly influence measurable improvements in teacher performance or student learning outcomes. Other factors, such as teacher motivation, instructional strategies, and student engagement, may have a more substantial impact. Meanwhile, one-way ANOVA results showed significant differences (p